Analysis of an average velocity of a pipe with flowing fluid in case of a hydraulic obstacle - Didžgalvis, Rimantas; Sudintas, Antanas; Tiknevičienė, Irena (Lietuvos matematikos rinkinys, 2000)
Calculation of average velocity of a fluid flow inside a pipe with an asymmetrical obstacle was carried out. Calculations consider flow maximum velocity co-ordinate to move in proportion with the obstacle thickness. The obtained ar44ticil average velocity expressions evaluate its change in accordance with the area of flow and obstacle interaction, i.e., in accordance with the change of hydraulic radius R and the obstacle (sediment) thickness. According to this, an average meaning of flow velocity is calculated, and pressure losses determined under it are considerably more precise.